Além dos estereótipos: a realidade dos trabalhadores braçais na área da construção civil na cidade de Birigui. - OLIVEIRA, Beatriz Aparecida de; CASAGRANDI, Maria Eduarda Carvalho; SOUZA, Nawani Martins de; MADEIRA, Pedro Santana (123, 2024)
O presente trabalho, intitulado "Além dos estereótipos: uma visão da população sobre os trabalhadores braçais na área da construção civil na cidade de Birigui", visa valorizar todos os trabalhadores que atuam no setor da construção. O objetivo é compreender a perspectiva da população em relação aos trabalhadores braçais e investigar se essa concepção está alinhada com a realidade. Através de questionários de aprofundamento científico, busca-se obter uma compreensão do cotidiano desses profissionais na área da construção civil e sua relação com o estigma social enfrentado. Como justificativa, argumenta-se que existe uma visão equivocada sobre os trabalhadores braçais, frequentemente associada a baixa remuneração, falta de formação e má conduta, entre outros aspectos negativos. Portanto, é importante refletir se existe ou não o preconceito associado a essa profissão e se é ou não necessário promover uma visão mais justa e respeitosa desses profissionais. A metodologia aplicada consiste em pesquisas de campo, utilizando um formulário enviado aos entrevistados por meio da plataforma Google Forms para a coleta de dados. Com o desenvolvimento deste artigo, almeja-se desmistificar o pensamento do corpo social em relação aos trabalhadores braçais, demonstrando a relevância e o significado desses profissionais no mercado de trabalho e no desenvolvimento da sociedade como um todo.

The present work, entitled "Beyond Stereotypes: The Population's View of Manual Laborers in the Construction Sector in the City of Birigui," aims to value all workers in the construction sector. The objective is to understand the population's perspective on manual laborers and investigate whether this perception aligns with reality. Through scientifically detailed questionnaires, this study seeks to gain an understanding of the daily lives of these professionals in the construction sector and their relationship with the social stigma they face. The justification argues that there is a misguided view of manual laborers, often associated with low pay, lack of education, and poor conduct, among other negative aspects. Therefore, it is important to reflect on whether there is prejudice associated with this profession and whether it is necessary to promote a fairer and more respectful view of these professionals. The applied methodology consists of field research using a questionnaire sent to respondents via the Google Forms platform to collect data. The development of this article aims to demystify the social body's perception of manual laborers, demonstrating the relevance and significance of these professionals in the labor market and the overall development of society. Industry and their relationship with the social stigma they face. As justification, it is argued that there is a mistaken view of manual workers, often associated with low pay, lack of training and misconduct, among other negative aspec ts. Therefore, it is important to reflect on the prejudice associated with this profession and promote a fairer and more respectful view of these professionals. The methodology applied consists of field research, using a form sent to interviewees through the Google Forms platform to collect data. The objective is to deepen the population's knowledge of professionals who work in this area. With the development of this article, we aim to demystify the thinking of the social body in relation to manual workers, demonstrating the relevance and significance of these professionals in the job market and in the development of society as a whole.
Beyond stereotypes: the reality of manual workers in the construction sector in the city of Birigui.
Keywords: Trabalhadores; Construção civil; Gestão e Negócios